Feasibility of Using the Hollow Glass Microsphere to Develop Lightweight CAC-GGBFS-Blended Strain-Hardening Cementitious Composites - Fan, Wei; Zhuge, Yan; Ma, Xing; Chow, Christopher W.K.; Gorjian, Nima; Liu, Yue (Frontiers in Materials, 2021)
Strain hardening cementitious composites (SHCC) has been utilised as an effective repair material with superior tensile strength and ductility. A corrosion-resistance binder, Calcium aluminate cement (CAC) - Ground granulated blast-furnace slag (GGBFS) blends, has been introduced into SHCC to expand its application in concrete sewerage networks rehabilitation. As a repair material, the lightweight property is particularly favourable as it can broader its functionality. This paper presents a study on developing a novel lightweight CAC-GGBFS blended strain hardening cementitious composites using Hollow Glass Microsphere (HGM), namely HGMLW-SHCC. Fine silica sand content was substituted with HGM at 25, 50, 75, 100 vol% in HGMLW-SHCC. Flowability, density, uniaxial compressive behaviour, direct tensile behaviour as well as pseudo strain-hardening indices we examined. Microstructure analysis was also conducted to understand the meso-scale behaviour of this new lightweight composite. The newly developed HGMLW-SHCC had a 28-day density of only 1756 kg/m3. Compressive and tensile strengths were determined in the range of 62.80–49.39 MPa and 5.81–4.19 MPa, respectively. All mixtures exhibited significant strain hardening behavior. Even though the increased HGM content negatively affected the tensile strength of HGMLW-SHCC, but it had a positive effect on its ductility. In addition, HGM can reduce crack width and tensile stress fluctuations significantly. Results showed that HGM was a promising material for producing strong and lightweight corrosion-resistance SHCC to be used as a retrofitting material in the wastewater industry.